Pegvisomant and not somatostatin receptor ligands (SRLs) is first-line medical therapy for acromegaly. Issue 6 (June 2020) - van der Lely, Aart J; Kuhn, Emmanuelle; Muhammad, Ammar; Coopmans, Eva C; Neggers, Sebastian J; Chanson, Philippe
Abstract : Current guidelines recommend the use of long-acting somatostatin receptor ligands (SRLs) first when surgery fails to correct GH/IGF-I hypersecretion in patients with acromegaly. In this issue of the journal, a pro- and contra debate will outline which arguments are in favour and which are against positioning pegvisomant (PEGV), a GH receptor antagonist, as the first-line treatment modality of acromegaly. The task of the pros was to promote a paradigm shift towards repositioning PEGV as first-line treatment as PEGV is safe and more effective than the first- and second-generation of SRLs. SRLs, when prescribed together with PEGV can still reduce tumour size when necessary, while they decrease the necessary dose of PEGV by around 50% in the average patient. They conclude that PEGV must move up towards the first-line treatment. For the cons, SRLs remain the first-line medical treatment. Indeed, even if, in recent studies, the remission rate is lower than initially claimed, SRLs are still effective not only for normalizing GH/IGF-I levels in half of the patients but also for inducing tumour shrinkage, improving comorbidities and headaches and reversing excess mortality. They are more convenient for use with their monthly administration and have a remarkable safety profile as demonstrated by the very prolonged experience acquired by more than 30 years of use. Finally, the cost-effectiveness of first-generation SRLs is better than that of PEGV. For all these reasons, cons consider that SRLs remain the best first medical treatment in patients requiring medical therapy.